A current survey of the corporate fitness programs and facilities in the United States - Hessil, Steven C.; Hessil, Steven C. (My University, 1985)
The purpose of this study was to up-date the status of Corporate Fitness Programs (CFPs) and to compare the results with previous study done by Bartsokas and St. Louis titled: Industrial Fitness Programs in the United States: A 1979 Status Study. A questionnaire was designed to gather statistical data and to compare the results in relation to the administration, organization, equipment and facilities, and evaluation of the CFPs. The survey was distributed to 100 of the 343 members of the Association for Fitness in Business, according to a stratified random sample of the eight regions of the United States. Fifty-eight of the 100 members surveyed were affiliated with corporations providing "in-house" facilities. Forty-eight of these programs were statistically analyzed.
Keywords: Employee fringe benefits -- United States; Health promotion -- United States